Development trajectories, emission profile, and policy actions: Singapore - Tilak K. Doshi; Neil Sebastian D'Souza (Asian Development Bank Institute (ADBI), 2013)
Singapore is the most industrialized and urbanized country in Southeast Asia and is totally dependent on oil and natural gas imports to satisfy its energy needs. Its national energy policy framework seeks to find a balance between maintaining Singapore's competitiveness, improving energy security, and enhancing environmental sustainability. In this paper, we discuss where Singapore stands with regard to its energy consumption and CO2 emissions, its energy policies to date, and those that will be implemented in the near future. We use a Singapore Energy- Economy model based on the Long Range Energy Alternatives Planning (LEAP) framework to assess the impact of energy efficiency and conservation policies on Singapore's energy intensity and CO2 emissions through to 2050. We also discuss the challenges that Singapore will face on account of climate change policies affecting key sectors of its economy. We find that Singapore has achieved much progress over the past four decades. Prudent energy policies and a changing economic structure have led to more efficient use of energy as evidenced by Singapore's declining energy intensity. There is considerable uncertainty as to the evolution of a global agreement on CO2 emissions reductions and the exact nature of the commitments that countries will be held to. Given Singapore's status as a preeminent shipping center and global oil refining center, CO2 emissions policies that will affect these industries will impact Singapore's economy if issues of "carbon leakage" are not adequately addressed.
Keywords: O53; Q38; Q45; Q48; 330; singapore; energy policy; energy consumption; co2 emissions; energy security; environmental sustainability; Energiekonsum; Luftverschmutzung; Treibhausgas-Emissionen; Energieversorgung; Energiepolitik; Klimawandel; Singapur